Improving Elementary Teacher’s Skills by Using Digital Tools for Interactive Learning - Liza Efriyanti, Liza Efriyanti; Sarwo Derta; Firdaus Annas; Sri Atiqah; Tiara Hardiana Putri; Sadar Martua Haholongan Sir; Muhammad Anis Muharram (Salus Publica: Journal of Community Service, 2025)
Improving the competence of teachers at Campago Ipuh Elementary School, Bukittinggi still faces challenges in utilizing technology for interactive learning. Along with the development of the era, the use of digital tools in the learning process is important to improve the quality of education. Therefore, training is needed for teachers to optimize the use of digital technology in teaching. The purpose of this service is to improve the competence of elementary school teachers in utilizing digital tools in interactive learning. The methodology used is training and mentoring in the form of workshops that teach the use of various digital learning applications, as well as providing simulations of the use of these tools in everyday learning. The results obtained show a significant increase in teachers' ability to use digital technology, especially in designing more interesting and effective interactive learning. Teachers are also more confident in integrating technology in the classroom. In conclusion, the use of digital tools has proven effective in improving teacher competence and learning quality. The recommendation from this activity is that similar training be carried out continuously and involve more teachers in other areas.